Rapid and Specific Detection of All Known Nipah virus Strains’ Sequences With Reverse Transcription-Loop-Mediated Isothermal Amplification - Ma, Liping; Chen, Zhen; Guan, Wuxiang; Chen, Quanjiao; Liu, Di (Frontiers in Microbiology, 2019)
Nipah virus (NiV) is a zoonotic virus and can be transmitted through contaminated food or directly between people. NiV is classified as a Biosesafety Level 4 agent not only because of its relatively high case fatslity rate, but also because there is no vaccine or other medical countermeasures and it appears to be transmitted by fomites/particulates. The development of rapid detection assay for NiV is of great importance because no effective field test is available. In this study, an isothermal (65 °C) reverse transcription-loop-mediated isothermal amplification (RT-LAMP) method was developed, targeting the nucleocapsid protein (N) gene, for the rapid detection of NiV, and was compared with conventional RT-PCR. Three pseudoviruses of NiV N gene representing all known strains were constructed to replace live NiV. A set of RT-LAMP primers, targeting a highly conserved region of N gene of the N gene in the viral genome was designed to identify all known NiV strains. Sensitivity tests indicated that the detection limit of the RT-LAMP assay was approximately 100 pg of total NiV pseudovirus RNA, which is at least 10-fold higher than that of conventional RT-PCR. Specificity tests showed that there was no cross-reactivity with nucleocapsid protein gene of Hendra virus, Newcastle disease virus, Japanese encephalitis virus, or Influenza A virus. The RT-LAMP assay provides results within 45 min, and requires no sophisticated instruments, except an isothermal water bath or metal bath with 1μl calcein indicator. An analysis of the clinical samples showed that the assay had good stability. In conclusion, systematic experiments have shown that the RT-LAMP assay developed here effectively detects three NiV pseudoviruses representing all known strains of NiV, with high specificity, sensitivity and stability.